Reducing Postpartum Oxycodone Usage at University Hospitals [33E]. (May 2020) - Cossler, Nancy; Liu, James H.; Albertini, Megan; Porter, Steven; Niemi, Marcie; Katz, Tyler Jessica
Abstract : INTRODUCTION: Opioid analgesics are among the most common medications employed for postpartum pain management. However, opioid side effects such as nausea, vomiting, urinary retention, and sedation are problematic and can adversely impact postpartum recovery. In addition, the national opioid crisis has prompted enhanced vigilance around narcotic usage in healthcare settings. Non-steroidal anti-inflammatory medications and acetaminophen are an effective complement to opioid analgesia. We describe a systematic approach to reducing postpartum oral narcotic use at MacDonald Women's Hospital (MWH), a northeast Ohio-based hospital providing obstetric services and delivering approximately 4000 women/year. METHODS: Beginning on June 5, 2018, we implemented a postpartum care bundle comprised of the following interventions: 1) Providing scheduled PO acetaminophen and PO ibuprofen every six hours after vaginal delivery; and 2) Providing scheduled IV ketorolac every 6 hours for twenty four hours after cesarean delivery, followed by scheduled PO acetaminophen and PO ibuprofen until discharge. RESULTS: From May 2017—May 2018, oxycodone usage at MacDonald Women's Hospital averaged 181.6 doses per 100 patient days. From June 2018—May 2019, average rates of oxycodone usage decreased to 153.3 doses per 100 patient days. Following the rollout of the postpartum care bundle, there was no significant change in Hospital Consumer Assessment of Healthcare Providers and Systems (HCAPS) patient satisfaction scores related to pain communication (77.9% 6 months pre-bundle vs. 92.2% 6 months post-bundle). CONCLUSION: This intervention was associated with a decrease in postpartum in-hospital oxycodone usage without a negative impact on patient satisfaction scores.